Acute gingival bleeding as a complication of dengue hemorrhagic fever - Saif Khan; N D Gupta; Sandhya Maheshwari (Wolters Kluwer Medknow Publications, 2013)
Dengue fever is mosquito borne disease caused by dengue virus (DENV) of Flaviviridae family. The clinical manifestations range from fever to severe hemorrhage, shock and death. Here, we report a case of 20-year-old male patient undergoing orthodontic treatment presenting with acute gingival bleeding with a history of fever, weakness, backache, retro orbital pain and ecchymosis over his right arm. The hematological investigations revealed anemia, thrombocytopenia and positive dengue non-structural protein-1 antigen and also positive immunoglobulin M and immunoglobulin G antibodies for DENV. Patient was diagnosed as a case of dengue hemorrhagic fever and was immediately referred for appropriate management. This case report emphasizes the importance of taking correct and thorough medical history.